قوانین نیب( دفعہ نمبر 01 تا 10)کا اسلامی تعلیما ت کی روشنی میں تجزیاتی مطالعہ: Analytical Study of NAB Laws (Sections 01 To 10) in The Light of Islamic Teachings - Muhammad Bilal; Saira Tariq; Muhammad Shoaib (Al Manhal Research Journal, 2025)
Allah Almighty made Islam the religion of nature and the religion of humanity. It guides all aspects of life, whether they are political or scientific, social or community, economic or moral. Especially in the teachings of Islam, accountability and distinguishing between what is lawful and what is unlawful in one’s actions are of fundamental importance. Therefore, in an Islamic society, no matter how powerful or weak a person is, he will definitely be held accountable for his actions. Islam, which is a complete code of life, has laid down a principle that everyone will be asked about their responsibilities. The more powerful a person is, the greater his sense of accountability for his responsibilities will be. As if accountability and giving an account of one’s actions is the basic foundation of Islam. No one can deny the importance of accountability in any society because accountability fulfills the basic requirements of justice in society. Nevertheless, accountability can gain importance only when people from every section of society see its application. Pakistan is an Islamic country, which is why various institutions have been established in it at different times for accountability, one of which is NAB. This article examines Articles 1 to 10 related to the powers of intention in the light of Islamic teachings.